A problematização do lixo eletrônico no ensino de química para o primeiro ano do ensino médio - ALMEIDA, Débora Quaresma (Universidade Federal do Pará, 2020)
The present paper entitled "CHEMISTRY IN MIDDLE SCHOOL: learning based on the problem of electronic waste" aims to understand how a teaching proposal based on the methodology of Problem Based Learning (PBL), can contribute to the teaching of chemistry in the first year of high school. The theoretical reference was built, mainly based on Ribeiro (2005), and other authors who are also references in the methodological field of the ABP, such as: Savin-Baden (2000), Berbel (1998), Malheiro (2005), Barrows 1996), Bruner (1987), Malheiro and Diniz (2008), among others. The methodology used in the development of this research was the qualitative approach of Gerhardt and Silveira (2009) of the oral research type, based on Connelly and Cladinin (1995). The subjects of the research were 03 chemistry teachers from a state public school in the municipality of Abaetetuba-PA. For the construction of the data, the proposal of teaching chemistry was given to the teachers, that is, the educational product built on the basis of the PBL, and the teachers were able to make their appreciation and analysis of the material by answering some questions present in an open questionnaire. The collected data were analyzed from the philosophical conceptions of Discursive Textual Analysis of Moraes and Galiazzi (2011). The results showed that, according to the teachers interviewed, the Educational Product, built from this dissertation, can contribute significantly to teaching-learning chemistry in high school, thus developing public school education in the municipality of Abaetetuba -PA.